Voros symbols as cluster coordinates. Issue 4 (10th May 2019) - Allegretti, Dylan G. L.
Abstract: We show that the Borel sums of the Voros symbols considered in the theory of exact WKB analysis arise naturally as Fock–Goncharov coordinates of framed P G L 2 ( C ) ‐local systems on a marked bordered surface. Using this result, we show that these Borel sums can be extended to meromorphic functions on C ∗, and we prove an asymptotic property of the monodromy map introduced in collaboration with Tom Bridgeland.